Math you can really use : - Herzog, David Alan (Wiley Pub., 2007)
Math You Can Really Use--Every Day skips mind-numbing theory and tiresome drills and gets right down to basic math that helps you do real-world stuff like figuring how much to tip, getting the best deals shopping, computing your gas mileage, and more. This is not your typical, dry math textbook. With a comfortable, easygoing approach, it: Covers math you'll need for balancing your checkbook, choosing or managing credit cards, comparing options for mortgages, insurance, and investments, and more. Includes the basics on fractions, decimals, percentages, measurements, and geometric math